Association of Obesity with Proteasomal Gene Polymorphisms in Children. (21st December 2013) - Kupca, Sarmite; Sjakste, Tatjana; Paramonova, Natalija; Sugoka, Olga; Rinkuza, Irena; Trapina, Ilva; Daugule, Ilva; Sipols, Alfred J.; Rumba-Rozenfelde, Ingrida
Abstract : The aim of this study was to ascertain possible associations between childhood obesity, its anthropometric and clinical parameters, and three loci of proteasomal genes rs2277460 ( PSMA6 c.-110C>A), rs1048990 ( PSMA6 c.-8C>G), and rs2348071 ( PSMA3 c. 543+138G>A) implicated in obesity-related diseases. Obese subjects included 94 otherwise healthy children in Latvia. Loci were genotyped and then analyzed using polymerase chain reactions, with results compared to those of 191 nonobese controls. PSMA3 SNP frequency differences between obese children and controls, while not reaching significance, suggested a trend. These differences, however, proved highly significant (P < 0.002 ) in the subset of children reporting a family history of obesity. Among obese children denying such history, PSMA6 c.-8C>G SNP differences, while being nonsignificant, likewise suggested a trend in comparison to the nonobese controls. No PSMA6 c.-110C>A SNP differences were detected in the obese group or its subsets. Finally, PSMA3 SNP differences were significantly associated (P < 0.05 ) with circulating low-density lipoprotein cholesterol (LDL) levels. Our results clearly implicate the PSMA3 gene locus as an obesity risk factor in those Latvian children with a family history of obesity. While being speculative, the clinical results are suggestive of altered circulatory LDL levels playing a possible role in the etiology of obesity in the young.